Kepastian Hukum Perjanjian Kredit Secara Elektronik Perbankan Ditinjau dari Aspek Hukum Perikatan - Fidelis Kurniawan Sugiarto (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Electronic credit facilities represent a significant banking innovation, employing technology in a manner that diverges from the established procedures associated with conventional credit. A credit deed that is not in accordance with the formal legal requirements is nevertheless considered to have legal force if the signature is recognized by the relevant parties. This thesis addresses the legal force and position of underhand credit agreements in commercial banks, as well as their suitability with the legal requirements of agreements according to the Civil Code and ITE Law, particularly in instances where the debtor subsequently rejects the signature. This thesis employs normative legal research methods to procure secondary data pertinent to the subject matter. The secondary data comprises primary, secondary, and tertiary legal materials, which are then subjected to qualitative analysis. The research demonstrates that the legal certainty of electronic credit agreements in commercial banks is regulated by the Civil Code Law Number 19 of 2016 on Electronic Information and Transactions, Government Regulation Number 71 of 2019 on the Implementation of Electronic Systems and Transactions, and OJK Regulation Number 38/POJK.03/2016 on the Application of Risk Management in the Use of Information Technology by Commercial Banks. In the event of a dispute over the rejection of an electronic signature in an agreement, the matter may be resolved through litigation after all other avenues of non-litigation have been exhausted. In electronic credit agreements, electronic signatures are recognized as valid evidence, thereby affording legal protection to creditors.